Association Between the Malnutrition Status and All‐Cause Mortality in Patients With Moderate and Severe Aortic Stenosis: A Prospective Cohort Study - Bingzhen Li; Shaozhao Zhang; Chaoguang Xu; Mengting Huang; Zhenyu Xiong; Ziwen Hui; Xinxue Liao; Jilin Li; Jianying Chen; Xiaodong Zhuang (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Malnutrition status is an important predictor of prognosis in patients after aortic valve replacement. However, the prognostic value of malnutrition status in patients with moderate‐to‐severe aortic stenosis is unclear. This study aimed to evaluate the effect of malnutrition on all‐cause mortality in patients with moderate‐to‐severe aortic stenosis using the Patient Controlled Nutritional Status (CONUT) score, nutritional risk index, and prognostic nutritional index. Methods and Results A total of 536 patients with moderate‐to‐severe aortic stenosis were selected in the ARISTOTLE (Aortic Valve Diseases Risk Factor Assessment and Prognosis Model Construction) study conducted between January 2013 and December 2022 in 3 academic institutions. Patients were grouped according to different nutritional status assessment methods. CONUT, nutritional risk index, and prognostic nutritional index were calculated at baseline. The primary study outcome was all‐cause mortality. Cox regression was used to assess the association between nutritional status and all‐cause mortality. During a median 34.2‐month follow‐up period, a total of 120 (22.4%) patients died. All‐cause mortality was significantly higher in lower prognostic nutritional index, lower nutritional risk index, and higher CONUT groups. Compared with normal nutrition, malnutrition was associated with an increased risk for all‐cause death (adjusted hazard ratio for mild and moderate–severe malnutrition, respectively: 2.82 [95% CI, 1.69–4.71; P<0.001] and 3.31 [95% CI, 1.74–6.32; P<0.001] for the CONUT). Conclusions In patients with moderate or severe aortic stenosis, we found that high CONUT scores, low nutritional risk index scores, and low prognostic nutritional index scores were associated with all‐cause death. The poorer the nutritional status, the greater the risk of malnutrition‐related all‐cause mortality. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT06069232.